L'egemonia costituente dei Quaderni del carcere di Gramsci - Pietro Maltese (Firenze University Press, 2013)
This paper discusses the category of Hegemony in Gramsci's theory and considers it a key to the interpretation of Subjectivity Growth. In Prison Notebooks, indeed, every hegemonic relationship, such as every political relationship, is necessarily a Pedagogic Relationship. Therefore, the studying of Hegemony like a construction device of subjectivity and society, ends by outlining a pedagogic theory, that helps to conceptualize the link between education and politics.